Plates of composite material, composite material with metal layer and method for manufacturing composite material with metal layer

CN122935476APending Publication Date: 2026-10-16NITTO DENKO CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202580021137.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-29
Filing Date
2025-03-27
Publication Date
2026-10-16

AI Technical Summary

Benefits of technology

本发明的复合材料在电路加工时的蚀刻、层叠压制导致的尺寸变化小,能够进行良好的电路加工,使用其的带金属层的复合材料能够防止层间偏移、电路短路等。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122935476A_ABST
    Figure CN122935476A_ABST
Patent Text Reader

Abstract

Provided is a composite material that is a metal layer-containing composite material that has a small dimensional change during etching and lamination pressing and enables good circuit processing during circuit processing. A plate-shaped composite material that contains a fluorine-based resin and a filler, has air pores enclosed therein, and has a tensile elastic modulus of 230 MPa or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a plate-shaped composite material suitable for use as a substrate for microstrip patch antennas such as millimeter-wave radar. Background Technology

[0002] In recent years, research and development on ADAS (Advanced Driver Assistance Systems) and autonomous driving has flourished in the automotive industry, and the importance of millimeter-wave radar, as a sensing technology supporting this research and development, has also increased. For automotive millimeter-wave radar, from the perspectives of small size, high performance, and low cost, the use of planar antennas with printed antenna elements (patches) on a resin substrate, known as "microstrip patch antennas," is promising. Research has been conducted on antenna pattern design and substrate materials to achieve higher performance.

[0003] As a substrate material for these antennas, polytetrafluoroethylene (PTFE) with a small dielectric loss tangent is one of the most promising materials. Furthermore, in order to improve mechanical, thermal and electrical properties, it has been proposed to combine it with granular fillers such as boron nitride, silicon dioxide, and titanium dioxide, as well as fillers such as glass fiber and carbon fiber (see Patent Documents 1 and 2).

[0004] Existing technical documents Patent documents Patent Document 1: Japanese Patent Application Publication No. 03-212987 Patent Document 2: Japanese Patent Application Publication No. 06-119810 Summary of the Invention

[0005] The problem that the invention aims to solve In the fabrication of multilayer laminates, such as those used for printed wiring antenna elements (patches) on resin substrates and for layered metal layers, high dimensional stability is required to ensure precise alignment of the patterns in each layer. However, fluoropolymers such as PTFE are prone to dimensional changes. When used as insulating materials, they tend to change in size before and after etching, which can lead to interlayer misalignment and short circuits.

[0006] Therefore, in this invention, a composite material for a composite material with a metal layer is provided, which, even when a fluorinated resin that is prone to dimensional changes is used as an insulating material, exhibits minimal dimensional changes during etching and lamination in circuit processing, and is capable of good circuit processing.

[0007] Solution for solving the problem In view of the above, the inventors have repeatedly conducted in-depth research and found that in composite materials with metal layers used for circuit processing, by making the composite material contain pores and having a tensile elastic modulus of less than 230 MPa, the dimensional changes caused by etching and lamination during circuit processing are small, and good circuit processing can be performed.

[0008] That is, the present invention has the following solution.

[0009] [1] A plate-shaped composite material, comprising a fluorinated resin and a filler, wherein the composite material contains pores and the tensile modulus of the composite material is 230 MPa or less.

[0010] [2] According to the plate-shaped composite material described in [1], wherein the fluorinated resin is polytetrafluoroethylene.

[0011] [3] The plate-shaped composite material according to [1] or [2], wherein the filler is silicon dioxide.

[0012] [4] According to the plate-shaped composite material described in [3], wherein the silica contains fumed silica and molten silica.

[0013] [5] A composite material with a metal layer, wherein at least one side of the plate-shaped composite material described in any of [1] to [4] has a metal layer.

[0014] [6] A method for manufacturing a composite material with a metal layer, which is a method for manufacturing the composite material with a metal layer as described in [5], wherein the method comprises the following steps: laminating a metal layer on a plate-shaped composite material; bonding by heating and pressurizing; and cooling at a cooling rate of less than 1°C / min.

[0015] [7] A method for manufacturing a composite material with a metal layer, which is a method for manufacturing the composite material with a metal layer as described in [5], wherein the method comprises the following steps: while maintaining the tension of the plate-shaped composite material before the metal layer is laminated, rolling is performed such that the pull-out tension relative to the MD direction is 10N or more and 50N or less and the winding tension is 10N or more and 20N or less, and the pull-out tension relative to the TD direction is 20N or more and 80N or less and the winding tension is 10N or more and 20N or less; laminating the metal layer on the plate-shaped composite material; bonding by heating and pressurizing; and cooling at a cooling rate of 5°C or less per minute.

[0016] Invention Effects The composite material of the present invention exhibits minimal dimensional changes due to etching and lamination during circuit processing, enabling excellent circuit fabrication. The composite material with a metal layer using this material can prevent interlayer misalignment, short circuits, and other issues. Attached Figure Description

[0017] Figure 1 The image is a SEM image of a porous inorganic microparticle aggregate formed by the aggregation of inorganic microparticles with an average primary particle size of 5-200 nm (the attached image is a substitute photograph). Detailed Implementation

[0018] The present invention will now be described based on examples of embodiments used to implement it. However, the present invention is not limited to the embodiments described below.

[0019] In this specification, "p and / or q (p and q are arbitrary configurations)" refers to at least one of p and q, and specifically to the three possibilities of p only, q only, and p and q.

[0020] In this specification, the terms “P or above” (where P is any number) or “Q or below” (where Q is any number) also include the meaning of “preferably greater than P” or “preferably less than Q”.

[0021] In this specification, the terms “P~Q” (where P and Q are arbitrary numbers) include “more than P and less than Q” unless otherwise specified, and also include “preferably more than P” or “preferably less than Q”.

[0022] In this specification, the numerical ranges described in stages can be arbitrarily combined with the upper or lower limits of the numerical ranges of other stages. Furthermore, the upper or lower limits of the numerical ranges described in this specification can also be replaced with the values ​​shown in the embodiments.

[0023] Plate-shaped composite materials As one aspect of the present invention, the plate-shaped composite material (hereinafter, sometimes simply referred to as "composite material") is a plate-shaped composite material containing a fluorinated resin and a filler, the composite material having pores, and the tensile modulus of elasticity of the composite material being 230 MPa or less.

[0024] The inventors have conducted repeated and in-depth studies on plate-shaped composite materials that can be used as substrates for microstrip patch antennas, etc., and have found that by including fluorine resin and filler in the composite material, containing pores and having a specific tensile modulus, residual strain generated during circuit processing can be suppressed, and heat transfer components can be placed in the precise position according to the design.

[0025] The following is a detailed explanation of "fluorinated resins" and "fillers".

[0026] Fluoropolymers There are no particular limitations on the types of fluorinated resins; fluorinated resins used for substrates, etc., can be appropriately used.

[0027] Fluorine-based resins commonly include polytetrafluoroethylene (PTFE), perfluoroalkoxyalkylene (PFA), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), polychlorotrifluoroethylene (PCTEF), tetrafluoroethylene-ethylene copolymer (ETFE), chlorotrifluoroethylene-ethylene copolymer (ECTFE), and polyvinylidene fluoride (PVDF), with PTFE being particularly preferred. One type or a combination of two or more of these resins may be used.

[0028] Fluoropolymer resins are preferably fibrillated (fibrous microstructure). More preferably, the fibers in the fibrillated resin are oriented not only in one direction but also in multiple directions, and particularly preferably, the fibrils are connected to the inorganic microparticle aggregates described later to form a "three-dimensional micromesh structure." When fluoropolymer resins are fibrillated, especially when a three-dimensional micromesh structure is formed, excellent mechanical strength and dimensional stability can be ensured as a composite material. It should be noted that the fibrillation of fluoropolymer resins can be confirmed by surface observation using SEM or similar methods. Furthermore, the fibrillation of fluoropolymer resins can be achieved, for example, by applying shear force; more specifically, it can be achieved through multi-stage rolling as described later, and the three-dimensional micromesh structure can be achieved through multi-stage rolling in different directions as described later.

[0029] <filler> In composite materials, inorganic microparticle aggregates and non-porous inorganic microparticles are preferred as fillers. Specifically, inorganic microparticle aggregates include... Figure 1 The SEM image shows an aggregate formed by the fusion of multiple inorganic particles, creating a porous structure with gaps between the particles. It should be noted that the inorganic particles in the aggregate only need to be fused during formulation; fusion can also be broken up through subsequent mixing with fluorinated resins.

[0030] On the other hand, the "aporous" in aporous inorganic particles refers to the characteristic expression of "porous" for inorganic particles. Aporous inorganic particles only need to be inorganic particles that are not "porous". That is, aporous inorganic particles do not need to be completely without pores. As long as they are not identified as "porous", they can have pores.

[0031] The following provides a detailed explanation of "inorganic microparticle aggregates" and "non-porous inorganic microparticles".

[0032] (Inorganic microparticle aggregates) The inorganic particles in inorganic particle aggregates are typically composed of oxides (including composite oxides) of typical elements such as silicon oxide (silica, etc.) and aluminum oxide; transition metal oxides (including composite oxides) such as titanium oxide (titanium dioxide, etc.), iron oxide, and zirconium oxide; and nitrides of typical elements such as boron nitride and silicon nitride. Oxides of typical elements are preferred, with silicon dioxide being particularly preferred. When the particles are oxides of typical elements, the relative permittivity of the composite material can be suppressed to an extremely low level, and the composite material can be manufactured at a lower cost. It should be noted that the crystallinity of the inorganic particles is not particularly limited, but in the case of silicon dioxide, they are usually amorphous.

[0033] The average primary particle size of the inorganic particles in the inorganic microparticle aggregate is typically 5-200 nm, preferably 10 nm or more, more preferably 15 nm or more, further preferably 20 nm or more, preferably 150 nm or less, more preferably 120 nm or less, further preferably 100 nm or less, particularly preferably 80 nm or less, and most preferably 70 nm or less. When within the above range, the inorganic microparticle aggregate is not easily destroyed even after mixing, molding, rolling, or other processing, ensuring good porosity between the inorganic particles, and easily ensuring a smooth surface as a plate-like composite material. It should be noted that the average primary particle size of the inorganic particles in the inorganic microparticle aggregate is a value obtained by observing and measuring the particle size using SEM and averaging the measured values. Specifically, the step involves randomly selecting 100 inorganic microparticle aggregates, measuring the particle size (major diameter of the particles) of each, and averaging the obtained particle sizes to obtain a value.

[0034] The average particle size of the primary aggregates of inorganic microparticles in the inorganic microparticle aggregate is typically 100 nm or more, preferably 120 nm or more, more preferably 150 nm or more, typically 400 nm or less, preferably 380 nm or less, more preferably 350 nm or less. The average particle size of the secondary aggregates (aggregates of primary aggregates) of inorganic microparticles in the inorganic microparticle aggregate is typically 0.1 μm or more, preferably 1 μm or more, more preferably 2 μm or more, typically 100 μm or less, preferably 90 μm or less, more preferably 80 μm or less. It should be noted that the inorganic microparticle aggregates in the composite material are preferably in the state of secondary aggregates. When in the state of secondary aggregates, the aforementioned three-dimensional fine mesh structure is easily formed. In addition, the average particle size of the primary aggregates and the average particle size of the secondary aggregates can be calculated using the same method as the average primary particle size of the inorganic microparticles in the inorganic microparticle aggregate described above.

[0035] The BET specific surface area of ​​inorganic particulate aggregates is typically 10 m².2 / g or more, preferably 20m 2 / g or more, preferably 30m 2 / g or more, further preferably 40m 2 / g or above, typically 250m 2 / g or less, preferably 240m 2 / g or less, more preferably 210m 2 / g or less, more preferably 150m 2 / g or less, especially preferably 80m 2 / g or less. When within the above range, the composite material can ensure high porosity and suppress the increase of dielectric loss tangent. In particular, when the BET specific surface area is too high, there is a tendency for the dielectric loss tangent of the composite material to become high. It should be noted that the BET specific surface area of ​​inorganic microparticle aggregates is a value calculated by substituting the amount of gas adsorbed by gas adsorption methods (especially nitrogen adsorption isotherms) into the BET formula, and is expressed as a value before the manufacture of the composite material.

[0036] The apparent specific gravity of the inorganic microparticle agglomerates is typically 10 g / L or higher, preferably 20 g / L or higher, more preferably 30 g / L or higher, even more preferably 40 g / L or higher, typically 100 g / L or lower, preferably 90 g / L or lower, more preferably 80 g / L or lower, even more preferably 70 g / L or lower, and particularly preferably 60 g / L or lower. When within the above range, the composite material ensures high porosity and the inorganic microparticle agglomerates are not easily destroyed. It should be noted that the apparent specific gravity of the inorganic microparticle agglomerates is obtained by filling the inorganic microparticle agglomerates into a container capable of measuring volume, such as a 250 mL graduated cylinder, measuring the filling mass (X g) and filling volume (Y mL), and dividing the filling mass by the filling volume ([apparent specific gravity (g / L)] = X / Y × 1000).

[0037] As an inorganic particulate aggregate, commercially available products such as the MIZUKASIL series (manufactured by Mizusawa Chemical Industry Co., Ltd.), SYLYSIA series (manufactured by Fuji SILYSIA Co., Ltd.), AEROSIL series (manufactured by AEROSIL Co., Ltd. of Japan) and Nipsil series (manufactured by TosohSilica Co., Ltd.) can be used appropriately. Among them, fumed silica from the AEROSIL series (manufactured by AEROSIL Co., Ltd. of Japan) is particularly preferred.

[0038] (Aporous inorganic particles) The materials of non-porous inorganic microparticles can typically include oxides of typical elements such as silicon oxide (silica, etc.) and aluminum oxide (including composite oxides); transition metal oxides such as titanium dioxide, iron oxide, and zirconium dioxide (also including composite oxides); and nitrides of typical elements such as boron nitride and silicon nitride, with silicon oxide being preferred. It should be noted that composite oxides include cordierite, talc, wollastonite, mullite, block talc, and forsterite. The materials of non-porous inorganic microparticles are not limited to one type and can also be a combination of two or more types.

[0039] The average primary particle size of the non-porous inorganic microparticles is typically 0.2 to 50 μm, preferably 0.3 μm or more, more preferably 0.4 μm or more, even more preferably 0.5 μm or more, preferably 40 μm or less, more preferably 30 μm or less, even more preferably 20 μm or less, particularly preferably 10 μm or less, and most preferably 5 μm or less. When within the above range, a suitable specific surface area is achieved, ensuring a good dielectric loss tangent, and the surface of the composite material is easily made smooth, making it a more suitable material for high-frequency substrates. It should be noted that the average primary particle size of the non-porous inorganic microparticles is a value obtained by observing and measuring the particle size using SEM and averaging the measured values. Specifically, this involves randomly selecting 100 inorganic microparticle aggregates, measuring the particle size (major diameter of the particles) of each, and averaging the obtained particle sizes to obtain the value.

[0040] The BET specific surface area of ​​non-porous inorganic microparticles is typically 0.1 m². 2 / g or more, preferably 0.5m 2 / g or more, preferably 1m 2 / g or more, further preferably 2m 2 / g or above, usually 30m 2 / g or less, preferably 25m 2 / g or less, more preferably 20m 2 / g or less, more preferably 15m 2 / g or less, especially preferably 10m 2 / g or less. When within the above range, a good dielectric loss tangent can be ensured, and the surface of the composite material can be easily made smooth, making it a more suitable material for substrates used in high-frequency applications. It should be noted that the BET specific surface area of ​​non-porous inorganic particles is a value calculated by substituting the amount of gas adsorbed, etc., measured by gas adsorption methods (especially nitrogen adsorption isotherms), into the BET formula, and is used as a numerical value before the manufacture of composite materials.

[0041] The relative permittivity of the non-porous inorganic microparticles is typically 10 or less, preferably 8 or less, more preferably 7 or less, even more preferably 6 or less, particularly preferably 5 or less, and typically 3 or more. It should be noted that the relative permittivity of the non-porous inorganic microparticles is a value determined by a method based on Japanese Industrial Standard JIS C2565.

[0042] Commercially available products that are non-porous inorganic microparticles include: fused silica such as SFP-130MC, SFP-30M, and FB-3SDC manufactured by Denka Co., Ltd.; cordierite powder of the FINE type, ELP-150N, and ELP-325N manufactured by AGC Ceramics Co., Ltd.; boron nitride such as FS-1, HP-P1, and HP40J series manufactured by Mizushima Alloy Iron Co., Ltd.; and talc such as NANO ACE D-600, D-800, D-1000, and FG-15 manufactured by Japan Talc Co., Ltd.

[0043] (Other fillers) Composite materials may include fillers that are not inorganic microparticle aggregates or non-porous inorganic microparticles (hereinafter sometimes referred to as "other fillers"). Preferably, the filler consists only of inorganic microparticle aggregates and non-porous inorganic microparticles. Examples of other fillers include granular fillers and fibrous fillers. Examples of granular fillers include solid carbon such as carbon black and graphite; and hollow inorganic particles such as silica spheres and glass spheres. Examples of fibrous fillers include glass fibers and carbon fibers. Other fillers are not limited to one type and may include combinations of two or more.

[0044] The filler (including inorganic microparticle aggregates and nonporous inorganic microparticles) is preferably modified with a surface modifier having hydrophobic groups (hereinafter sometimes simply referred to as "surface modifier").

[0045] The following section provides a detailed explanation of modifications based on "surface modifiers".

[0046] Hydrophobic groups used as surface modifiers include fluorine groups (-F) and hydrocarbon groups (-C). n H 2n+1 (n=1~30) etc., especially fluorinated groups that exhibit liquefaction not only to water but also to oils are preferred.

[0047] Surface modifiers can be substances that chemically adsorb (react) onto the surface of a filler, or substances that physically adsorb onto the surface of a filler. They can be low-molecular-weight compounds or high-molecular-weight compounds. Surface modifiers that chemically adsorb (react) onto the surface of a filler typically possess reactive functional groups that react with the surface functional groups (hydroxyl groups (-OH), etc.) of the filler. Examples of reactive functional groups include alkoxysilyl groups (-SiOR (R has 1-6 carbon atoms)), chlorosilyl groups (-SiCl), bromosilyl groups (-SiBr), and hydrosilyl groups (-SiH). It should be noted that the method of modifying the surface of a filler with a surface modifier can appropriately employ known methods, such as bringing the filler into contact with the surface modifier.

[0048] Surface modifiers can be used in one or in combination of two or more. For example, a surface modifier of a low molecular weight compound with reactive functional groups can react with the surface of the filler, and then a surface modifier of a high molecular weight compound with hydrophobic groups can be physically adsorbed onto it. When the filler is made of silica or similar materials, it may sometimes dissolve (decompose) when exposed to alkaline aqueous solutions. Modification in this way can improve the resistance to alkaline aqueous solutions.

[0049] The thermal decomposition temperature of the surface modifier is typically 250°C or higher, preferably 300°C or higher, more preferably 350°C or higher, even more preferably 360°C or higher, and particularly preferably 370°C or higher. When within the above range, decomposition can be suppressed even by high-temperature heating or other treatments. The thermal decomposition temperature of the surface modifier is set as the temperature at which a 5% weight loss occurs when the temperature is increased by 20°C / min using thermogravimetric analysis (TG-DTA).

[0050] As surface modifiers for low-molecular-weight compounds with fluorine groups and reactive functional groups, examples of surface modifiers represented by the following formulas can be listed. It should be noted that the compounds shown in the following formulas are commercially available and can be suitably obtained for use as surface modifiers. As surface modifiers for polymers with fluorine groups, examples of surface modifiers shown in the following formulas can be listed. [In the above formula, n and m are positive numbers.] Commercially available solutions can be used as surface modifiers. Suitable surface modifiers include T1770 manufactured by Tokyo Chemical Industry Co., Ltd., and Novec (registered trademark) 2202 manufactured by 3M Corporation. Novec (registered trademark) 2202 discloses a polymer compound containing a fluorine group, combined with a "fluoroalkyl silane polymer". When using Novec (registered trademark) 2202 as a surface modifier, it has the advantage of easily and simply suppressing the critical hydrophobic tension of the composite material.

[0051] The content of surface modifier (organic content) in the filler is generally 0.1% by mass or more, preferably 1% by mass or more, more preferably 2% by mass or more, further preferably 3% by mass or more, particularly preferably 4% by mass or more, generally 50% by mass or less, preferably 40% by mass or less, more preferably 30% by mass or less, further preferably 25% by mass or less, particularly preferably 20% by mass or less.

[0052] <Composite Materials> The composite material contains fibrils made of the aforementioned fluorinated resin and fillers, and may be manufactured using composite material compositions containing other raw materials as needed. The composite material will be described below.

[0053] In the composite material, the total content of inorganic microparticle aggregates and non-porous inorganic microparticles is preferably 20 to 90% by mass, more preferably 30% by mass or more, even more preferably 40% by mass or more, particularly preferably 50% by mass or more, more preferably 80% by mass or less, even more preferably 75% by mass or less, and particularly preferably 70% by mass or less.

[0054] Here, "total content" refers to the combined content of inorganic microparticle aggregates and non-porous inorganic microparticles when the composite material is set to 100% by mass. When the composite material contains two or more types of inorganic microparticle aggregates and / or non-porous inorganic microparticles, it refers to their total content. Furthermore, when the fluorinated resin and the total content of inorganic microparticle aggregates and non-porous inorganic microparticles are set to 100% by mass, the total content of inorganic microparticle aggregates and non-porous inorganic microparticles is generally preferably 20-90% by mass, more preferably 30% by mass or more, further preferably 40% by mass or more, particularly preferably 50% by mass or more, more preferably 80% by mass or less, further preferably 75% by mass or less, and particularly preferably 70% by mass or less. When within the above ranges, various properties such as relative permittivity and dielectric loss tangent become easier to coordinate.

[0055] In the composite material, the mass ratio of the content of the aforementioned non-porous inorganic microparticles to the total content of inorganic microparticle aggregates and the aforementioned non-porous inorganic microparticles [content of the aforementioned non-porous inorganic microparticles / (content of the aforementioned inorganic microparticle aggregates + content of the aforementioned non-porous inorganic microparticles)] is preferably 0.15 to 0.90, more preferably 0.2 or more, further preferably 0.3 or more, particularly preferably 0.4 or more, most preferably 0.5 or more, more preferably 0.8 or less, further preferably 0.75 or less, particularly preferably 0.7 or less, and most preferably 0.65 or less.

[0056] The total content of fillers in composite materials is typically 20-90% by mass, preferably 30% by mass or more, more preferably 40% by mass or more, even more preferably 50% by mass or more, preferably 80% by mass or less, more preferably 75% by mass or less, and even more preferably 70% by mass or less.

[0057] Furthermore, when the total content of fluorinated resin and filler is set to 100% by mass, the total content of filler is typically preferred to be 20-90% by mass, more preferably 30% by mass or more, even more preferably 40% by mass or more, particularly preferably 50% by mass or more, more preferably 80% by mass or less, even more preferably 75% by mass or less, and particularly preferably 70% by mass or less. When within the above ranges, various properties such as relative permittivity and dielectric loss tangent become easier to coordinate.

[0058] The composite material may contain substances other than the fluorinated resin and filler (including inorganic microparticle aggregates and nonporous inorganic microparticles) mentioned above. The total content of fluorinated resin and filler in the composite material is usually 60% by mass or more, preferably 70% by mass or more, more preferably 80% by mass or more, further preferably 90% by mass or more, and particularly preferably 100% by mass.

[0059] The composite material is plate-shaped, with a thickness typically ranging from 2.0 to 3000 μm, preferably 10 μm or more, more preferably 50 μm or more, further preferably 80 μm or more, most preferably 90 μm or more, preferably 2000 μm or less, more preferably 1000 μm or less, further preferably 800 μm or less, particularly preferably 600 μm or less, and most preferably 400 μm or less. When within the above ranges, the composite material can ensure good relative permittivity, etc.

[0060] The dimensions (maximum diameter, longitudinal or transverse length) of the composite material are typically 20 to 1500 mm, preferably 30 mm or more, more preferably 40 mm or more, even more preferably 50 mm or more, most preferably 60 mm or more, preferably 1400 mm or less, and more preferably 1300 mm or less.

[0061] The composite material contains pores, and the porosity of the composite material is typically 10-90% by volume, preferably 15% by volume or more, more preferably 20% by volume or more, further preferably 30% by volume or more, particularly preferably 40% by volume or more, preferably 80% by volume or less, more preferably 70% by volume or less, further preferably 60% by volume or less, and particularly preferably 55% by volume or less. When within the above ranges, the composite material can ensure good properties such as relative permittivity and coefficient of thermal expansion.

[0062] The porosity of the composite material is calculated by measuring the volume of the composite material, the specific gravity and mass (compound mass) of the fluorinated resin, and the specific gravity and mass (compound mass) of the filler, and then substituting these values ​​into the following formula.

[0063] [Porosity (volume %)] = ([Volume of composite material] - [Mass of fluorinated resin / Specific gravity of fluorinated resin] - [Mass of filler / Specific gravity of filler]) / [Volume of composite material] × 100 The tensile strength of the composite material is typically 1 to 50 MPa, preferably 5 MPa or more, more preferably 7 MPa or more, even more preferably 10 MPa or more, preferably 45 MPa or less, more preferably 40 MPa or less, and even more preferably 35 MPa or less. The tensile strength is a value determined according to the method specified in Japanese Industrial Standard JIS K7161 (detailed conditions are described below).

[0064] The tensile modulus of the composite material is 230 MPa or less, preferably 120 to 228 MPa, more preferably 125 MPa or more, even more preferably 130 MPa or more, particularly preferably 135 MPa or more, even more preferably 140 MPa or more, preferably 225 MPa or less, and more preferably 223 MPa or less. When it is within the above range, it can be achieved by reducing the residual stress generated during the cooling of the composite material. The tensile modulus of elasticity is a value measured according to the method specified in Japanese Industrial Standard JIS K7161 (detailed conditions are described below).

[0065] The relative permittivity (frequency: 10 GHz) of the composite material is typically 3.0 or less, preferably 2.60 or less, more preferably 2.40 or less, even more preferably 2.00 or less, particularly preferably 1.80 or less, and typically 1.55 or more. It should be noted that the relative permittivity of the composite material is set as the value of the real part (εr') calculated by measuring the complex permittivity using the cavity resonator perturbation method (measurement frequency: 10 GHz).

[0066] The dielectric loss tangent (frequency: 10 GHz) of the composite material is typically 0.01 or less, preferably 0.008 or less, more preferably 0.006 or less, even more preferably 0.004 or less, particularly preferably 0.002 or less, and typically 0.0005 or more. It should be noted that the relative permittivity of the composite material is set as the ratio (εr” / εr’) of the imaginary part (εr”) to the real part (εr’) calculated by measuring the complex permittivity using the cavity resonator perturbation method (measurement frequency: 10 GHz).

[0067] The coefficient of thermal expansion (Z-axis direction) of the composite material is typically below 100 ppm / K, preferably below 90 ppm / K, more preferably below 80 ppm / K, even more preferably below 70 ppm / K, particularly preferably below 60 ppm / K, most preferably below 50 ppm / K, and typically above 5 ppm / K. It should be noted that the coefficient of thermal expansion (Z-axis direction) of the composite material is calculated using laser interferometry (laser dilatometer, measurement temperature range: -50~200℃, heating rate: 2℃ / min, atmosphere: He, load: 17g) according to the formula in Japanese Industrial Standard JIS R3251:1990.

[0068] The smaller the dimensional change rate of the composite material, the better; it is generally below 1000 ppm, preferably below 900 ppm, more preferably below 800 ppm, further preferably below 700 ppm, particularly preferably below 600 ppm, and generally above 0 ppm. It should be noted that the dimensional change rate of the composite material refers to the rate of change of distance from the origin to the measurement point before and after etching of the composite material with the metal layer (detailed conditions are described below).

[0069] Applications of composite materials The applications of the composite material are not particularly limited, but electronic circuit boards are preferred, and circuit boards for mobile phones, computers, etc., and substrates for microstrip patch antennas for millimeter-wave radar are more preferred. That is, as one aspect of the present invention, substrates containing the above-mentioned composite material (hereinafter sometimes simply referred to as "substrate") may also be listed.

[0070] The substrate is made of a composite material, and preferably has a layer (hereinafter sometimes simply referred to as "resin layer") made of a thermoplastic resin adhered to one or both sides of the composite material. Fluorine resin is particularly preferred as the thermoplastic resin.

[0071] Examples of fluorinated resins include polytetrafluoroethylene (PTFE, melting point: 327℃), perfluoroalkoxyalkane (PFA, melting point: 310℃), tetrafluoroethylene-hexafluoropropylene copolymer (FEP, melting point: 260℃), polychlorotrifluoroethylene (PCTEF, melting point: 220℃), tetrafluoroethylene-ethylene copolymer (ETFE, melting point: 270℃), chlorotrifluoroethylene-ethylene copolymer (ECTFE, melting point: 270℃), and polyvinylidene fluoride (PVDF, melting point: 151~178℃), with PTFE and PFA being particularly preferred. One type or two or more types can be used in combination.

[0072] The thickness of the resin layer is typically 0.050 to 30 μm, preferably 0.100 μm or more, more preferably 0.40 μm or more, further preferably 1.0 μm or more, most preferably 1.5 μm or more, preferably 20 μm or less, more preferably 10 μm or less, further preferably 8.0 μm or less, particularly preferably 6.0 μm or less, and most preferably 5.0 μm or less. The substrate is exposed to various chemicals used in the manufacturing processes of antennas, etc. For example, when exposed to highly permeable processing solutions, the processing solution may sometimes penetrate into the substrate, causing appearance defects and changes in properties. The resin layer also has the function of inhibiting the penetration of processing solutions; therefore, when within the above range, it can effectively inhibit the peeling of metal layers, etc., and even when exposed to highly permeable processing solutions used in the manufacturing of electronic circuit boards, appearance defects and changes in properties are less likely to occur. It should be noted that the thickness of the resin layer refers to a value obtained by measuring approximately 5 to 10 points from the end of the resin layer in the thickness direction to the interface between the composite material and the resin layer and averaging these measurements.

[0073] The resin layer can be laminated (bonded) on one side of the composite material or on both sides of the composite material.

[0074] The peel strength between the composite material and the resin layer is typically 0.2 to 2.5 N / mm, preferably 0.3 N / mm or more, more preferably 0.4 N / mm or more, even more preferably 0.5 N / mm or more, preferably 2.4 N / mm or less, more preferably 2.2 N / mm or less, and even more preferably 2 N / mm or less. The peel strength is a value measured according to the method specified in Japanese Industrial Standard JIS C6481:1996 (detailed conditions are described below).

[0075] A metal layer is typically disposed on the substrate. It should be noted that, in the case of a resin layer, the metal layer is stacked on top of the resin layer.

[0076] The metal types that can be included in a metal layer typically include gold (Au), silver (Ag), platinum (Pt), copper (Cu), aluminum (Al), and alloys containing these metal types.

[0077] The thickness of the metal layer is typically 5 μm or more, preferably 10 μm or more, more preferably 15 μm or more, typically 50 μm or less, preferably 45 μm or less, more preferably 40 μm or less.

[0078] The maximum height Rz of the contact surface between the metal layer and the composite material or resin layer is typically 0.020 μm or more, preferably 0.050 μm or more, more preferably 0.10 μm or more, further preferably 0.20 μm or more, particularly preferably 0.30 μm or more, typically 10 μm or less, preferably 8.0 μm or less, more preferably 6.0 μm or less, further preferably 4.0 μm or less, and particularly preferably 2.0 μm or less. It should be noted that "maximum height Rz" refers to a value determined according to the method of Japanese Industrial Standard JIS B0601:2013 (a Japanese Industrial Standard created to replace the technical content of International Organization for Standardization standard ISO 4287 without changing its technical content). In addition, besides direct measurement, the maximum height Rz of the material used for the metal layer can also be used directly for "maximum height Rz of the contact surface between the metal layer and the composite material or resin layer".

[0079] The thickness obtained by subtracting the maximum height Rz of the metal layer from the thickness of the resin layer ((resin layer thickness) - (maximum height Rz of the metal layer)) is typically 0.005 μm or more, preferably 0.010 μm or more, more preferably 0.050 μm or more, even more preferably 0.10 μm or more, particularly preferably 0.50 μm or more, typically 29.98 μm or less, preferably 20 μm or less, more preferably 15 μm or less, even more preferably 10 μm or less, and particularly preferably 5.0 μm or less. When it is within the above range, the thickness of the resin layer can be sufficiently ensured, so even when exposed to highly permeable processing solutions used in the manufacture of electronic circuit boards, it is not easy to produce appearance defects or changes in properties.

[0080] <Methods for manufacturing composite materials> The composite material is preferably manufactured by a manufacturing method including the following resin preparation process, filler preparation process, mixing process, molding process and rolling process.

[0081] • Resin preparation process for preparing fluorinated resins (hereinafter, sometimes simply referred to as "resin preparation process").

[0082] • The filler preparation process (hereinafter sometimes simply referred to as the "filler preparation process").

[0083] • The mixing process of mixing the above-mentioned fluorinated resin, the above-mentioned filler and volatile additive to obtain the precursor composition (hereinafter, sometimes simply referred to as the "mixing process").

[0084] • A forming process in which the above-mentioned precursor composition is formed to obtain a rollable object (hereinafter, sometimes simply referred to as "forming process").

[0085] • The rolling process of rolling the above-mentioned material to obtain the composite material (hereinafter, sometimes simply referred to as the "rolling process").

[0086] The following provides a detailed explanation of the "resin preparation process", "filler preparation process", "mixing process", "molding process", and "rolling process".

[0087] The resin preparation process involves preparing the fluorinated resin, which can be obtained or manufactured in-house. The average particle size (median particle size d50) of the prepared fluorinated resin granules (particles after secondary particles) is typically 0.5 μm or more, preferably 1.0 μm or more, more preferably 10 μm or more, further preferably 30 μm or more, typically 700 μm or less, preferably 300 μm or less, more preferably 150 μm or less, further preferably 100 μm or less, and particularly preferably 50 μm or less. When within the above range, it is easy to uniformly disperse the fluorinated resin and filler. It should be noted that the fluorinated resin granules can be determined according to the method of Japanese Industrial Standard JIS Z8825:2001.

[0088] The filler preparation process involves preparing the filler. The filler (including inorganic microparticle aggregates and non-porous inorganic microparticles) can be obtained or manufactured in-house. The average particle size (median particle size d50) of the prepared filler, particularly the granulated inorganic microparticle aggregates (particles after secondary particles), is typically 0.1 μm or more, preferably 0.5 μm or more, more preferably 1 μm or more, further preferably 3 μm or more, typically 500 μm or less, preferably 200 μm or less, more preferably 100 μm or less, further preferably 50 μm or less, and particularly preferably 20 μm or less. The average particle size (median particle size d50) of the granulated non-porous inorganic microparticles (particles after secondary particles) is typically 1 μm or more, preferably 3 μm or more, more preferably 5 μm or more, further preferably 10 μm or more, typically 2000 μm or less, preferably 1000 μm or less, more preferably 500 μm or less, further preferably 100 μm or less, and particularly preferably 50 μm or less. When within the above range, it is easy to uniformly disperse the fluorinated resin and filler. It should be noted that the filler granulation composition can be determined according to the method of Japanese Industrial Standard JIS Z8825:2001.

[0089] In addition, the filler is preferably a surface modifier as described above.

[0090] The particle size ratio of the average particle size of the prepared fluorinated resin granules to the average particle size of the inorganic microparticle aggregates [average particle size of the fluorinated resin (median particle size d50) / average particle size of the inorganic microparticle aggregates (median particle size d50)] is typically 150 or less, preferably 100 or less, more preferably 60 or less, further preferably 40 or less, particularly preferably 30 or less, most preferably 10 or less, and typically 1 or more. The particle size ratio of the average particle size of the prepared fluorinated resin granules to the average particle size of the non-porous inorganic microparticles (average particle size of the fluorinated resin (median particle size d50) / average particle size of the non-porous inorganic microparticles (median particle size d50)) is typically 500 or less, preferably 300 or less, more preferably 200 or less, further preferably 100 or less, particularly preferably 50 or less, most preferably 30 or less, and typically 0.01 or more. When within the above ranges, it is easy to uniformly disperse the fluorinated resin and the filler.

[0091] The mixing process is the process of mixing fluorinated resins, fillers and volatile additives to obtain a precursor composition. The mixing can be carried out by known methods such as dry mixing or wet mixing, or by using a mixer.

[0092] In dry applications, the rotational speed (circumferential speed) of the agitator, etc., is typically 0.5 m / sec or more, preferably 1 m / sec or more, more preferably 5 m / sec or more, even more preferably 10 m / sec or more, particularly preferably 15 m / sec or more, typically 200 m / sec or less, preferably 180 m / sec or less, more preferably 140 m / sec or less, even more preferably 100 m / sec or less, particularly preferably 50 m / sec or less, and most preferably 20 m / sec or less. When within the above ranges, it is easy to uniformly disperse the fluoropolymer resin and filler.

[0093] In the dry mixing case, the mixing time is typically 10 seconds or more, preferably 20 seconds or more, more preferably 30 seconds or more, further preferably 40 seconds or more, particularly preferably 1 minute or more, most preferably 5 minutes or more, typically 60 minutes or less, preferably 50 minutes or less, more preferably 40 minutes or less, further preferably 30 minutes or less, particularly preferably 20 minutes or less, and most preferably 15 minutes or less. When within the above ranges, it is easy to uniformly disperse the fluoropolymer resin and filler.

[0094] In wet applications, the rotational speed (circumferential speed) of the agitator, etc., is typically 1 m / sec or more, preferably 5 m / sec or more, more preferably 10 m / sec or more, further preferably 15 m / sec or more, particularly preferably 20 m / sec or more, most preferably 25 m / sec or more, typically 160 m / sec or less, preferably 130 m / sec or less, more preferably 100 m / sec or less, further preferably 80 m / sec or less, particularly preferably 60 m / sec or less, and most preferably 40 m / sec or less. When within the above ranges, it is easy to uniformly disperse the fluoropolymer resin and filler.

[0095] In the wet process, the mixing time is typically 5 seconds or more, preferably 10 seconds or more, more preferably 20 seconds or more, further preferably 30 seconds or more, particularly preferably 40 seconds or more, and most preferably 50 seconds or more. It is typically 60 minutes or less, preferably 50 minutes or less, more preferably 40 minutes or less, further preferably 20 minutes or less, particularly preferably 10 minutes or less, and most preferably 5 minutes or less. When within the above ranges, it is easy to uniformly disperse the fluoropolymer resin and filler.

[0096] Volatile additives have the function of removing them by eventually volatilizing, thereby ensuring sufficient internal pores in the composite material. Volatile additives refer to compounds with a boiling point of 30-300°C that are liquid at room temperature (25°C). The boiling point of the volatile additive is preferably 50°C or higher, more preferably 100°C or higher, even more preferably 200°C or higher, preferably 280°C or lower, more preferably 260°C or lower, and even more preferably 240°C or lower.

[0097] Types of volatile additives include hydrocarbons, ethers, esters, and alcohols with low reactivity, with aliphatic saturated hydrocarbons being preferred. Specifically, examples include hexane (boiling point: 69℃), heptane (boiling point: 98℃), octane (boiling point: 126℃), nonane (boiling point: 151℃), decane (boiling point: 174℃), undecane (boiling point: 196℃), dodecane (boiling point: 215℃), tridecane (boiling point: 234℃), and tetradecane (boiling point: 254℃). One type or two or more can be used in combination.

[0098] When the total amount of fluorinated resin and filler is set to 100% by mass, the amount of volatile additive added is typically 1% by mass or more, preferably 5% by mass or more, more preferably 10% by mass or more, further preferably 20% by mass or more, particularly preferably 30% by mass or more, typically 200% by mass or less, preferably 150% by mass or less, more preferably 130% by mass or less, further preferably 110% by mass or less, and particularly preferably 100% by mass or less. When within the above ranges, good porosity can be ensured as a composite material.

[0099] In the mixing process, it is preferable to add a solvent in addition to the fluorinated resin, filler, and volatile additives. The solvent has the function of enabling the precursor composition to be uniformly dispersed into a paste. Examples of solvents include water, methanol, ethanol, isopropanol, butanol, and other lower alcohols. One or more of them can be used.

[0100] The forming process is the process of shaping the precursor composition to obtain a rollable material. Examples of forming machines used in the forming process include FT dies (fishtail extrusion dies), presses, extrusion molding machines, and calendering rollers. FT dies are particularly preferred.

[0101] The rolling process is a process of rolling a workpiece to obtain a composite material. Preferably, it is a "multi-stage rolling" process in which the resulting rolled workpieces are repeatedly stacked and rolled multiple times. Particularly preferred is a "multi-stage rolling in different directions" process in which the workpiece is rolled in a direction different from the previous rolling direction. For example, a multi-stage rolling process in different directions can be described by repeatedly performing the following operation: stacking the rolled workpieces in the same rolling direction, and then rotating the rolling direction of the workpiece by 90° from the previous rolling direction.

[0102] The number of layers of rolled material in multi-stage rolling is usually 2 or more, preferably 3 or more, more preferably 4 or more, even more preferably 10 or more, particularly preferably 30 or more, usually 10,000 or less, preferably 2,500 or less, more preferably 700 or less, even more preferably 500 or less, and particularly preferably 300 or less.

[0103] The rolling ratio of the rolling process is usually 10 or more, preferably 20 or more, more preferably 40 or more, even more preferably 50 or more, especially preferably 100 or more, usually less than 20,000, preferably less than 15,000, more preferably less than 10,000, even more preferably less than 5,000, and especially preferably less than 3,000.

[0104] In the rolling process, it is preferable to apply tension such that the tension of the rolled material (the plate-shaped composite material before the stacked metal layers) is 10N or more and 50N or less in the pull-out tension relative to the MD direction and 10N or more and 20N or less in the winding tension.

[0105] Furthermore, it is preferable to apply tension in a manner that the extraction tension relative to the TD direction is 20N to 80N and the winding tension is 10N to 20N.

[0106] More preferably, the tensions in both the MD and TD directions are maintained at specific tensions (extraction / winding), thereby enabling the desired tensile modulus / dimensional changes to be achieved even with the quenching described later (typically at a rate of less than 5°C / min).

[0107] Examples of devices used in the rolling process include presses, extrusion molding machines, and rolling rolls (such as calendering rolls).

[0108] The manufacturing method of the composite material or the substrate may also include other steps, specifically the following steps.

[0109] • An additive removal process (hereinafter sometimes simply referred to as "additive removal process") for removing the volatile additives from the rolled product.

[0110] • The heating and compression process that heats and compresses the above-mentioned rolled material (hereinafter, sometimes simply referred to as the "heating and compression process").

[0111] • A resin layer forming process (hereinafter sometimes simply referred to as "resin layer forming process") in which a resin layer containing a fluorine-based resin is formed on one or both sides of the above composite material.

[0112] Other layer forming processes (hereinafter sometimes simply referred to as "metal layer forming processes") that form a metal layer on one or both sides of the above composite material.

[0113] • A patterning process for patterning the above-mentioned metal layer (hereinafter, sometimes simply referred to as "patterning process").

[0114] The following provides a detailed explanation of the "additive removal process", "heating and compression process", "resin layer formation process", "metal layer formation process", and "patterning process".

[0115] The additive removal process is the process of removing the aforementioned volatile additives from the rolled product. A common method is to heat the rolled product in a furnace suitable for drying. The heating conditions can be appropriately selected based on the boiling point of the volatile additives, etc.

[0116] The heating and compression process involves heating and compressing the rolled material. Common methods include using a press or similar equipment. The heating and compression conditions can be appropriately selected, with uniform pressure applied throughout the surface of the rolled material being preferred.

[0117] The resin layer forming process involves forming a resin layer containing a fluorinated resin on one or both sides of a composite material. Examples of resin layer formation include heating and pressurizing a resin film containing a fluorinated resin using a press or similar device to bond it to the composite material. More preferably, a metal layer is heated and pressurized to bond it to the composite material through the resin film. By heating and pressurizing the metal layer onto the composite material through the resin film containing the fluorinated resin, the fluorinated resin penetrates into the composite material, effectively suppressing the peeling of the metal layer and ensuring a good relative permittivity for the composite material.

[0118] The thickness of the resin film containing fluorinated resin is generally 0.050 μm or more, preferably 0.10 μm or more, more preferably 0.40 μm or more, even more preferably 1.0 μm or more, particularly preferably 1.5 μm or more, generally 30 μm or less, preferably 20 μm or less, more preferably 10 μm or less, even more preferably 8.0 μm or less, particularly preferably 6.0 μm or less, and most preferably 5.0 μm or less.

[0119] The pressure during the resin layer formation process is typically 0.01 MPa or higher, preferably 0.10 MPa or higher, more preferably 0.50 MPa or higher, even more preferably 0.80 MPa or higher, particularly preferably 1.00 MPa or higher, typically 50 MPa or lower, preferably 40 MPa or lower, more preferably 30 MPa or lower, even more preferably 20 MPa or lower, and particularly preferably 10 MPa or lower. When within the above ranges, peeling of metal layers, etc., can be effectively suppressed, and as a composite material, a good relative permittivity, etc., can be ensured.

[0120] The temperature during the resin layer formation process is typically 250°C or higher, preferably 280°C or higher, more preferably 300°C or higher, even more preferably 320°C or higher, particularly preferably 340°C or higher, typically 500°C or lower, preferably 480°C or lower, more preferably 460°C or lower, even more preferably 440°C or lower, and particularly preferably 420°C or lower. When within the above ranges, peeling of metal layers, etc., can be effectively suppressed, and as a composite material, a good relative permittivity, etc., can be ensured.

[0121] The heating and pressurizing time in the resin layer formation process is typically 1 second or more, preferably 30 seconds or more, more preferably 1 minute or more, further preferably 2 minutes or more, particularly preferably 3 minutes or more, typically 180 minutes or less, preferably 120 minutes or less, more preferably 60 minutes or less, further preferably 30 minutes or less, and particularly preferably 20 minutes or less. When within the above ranges, peeling of metal layers, etc., can be effectively suppressed, and as a composite material, a good relative permittivity, etc., can be ensured.

[0122] Examples of equipment used in the resin layer formation process include presses, hot roller laminators, and belt presses.

[0123] The metal layer forming process is a process of forming a metal layer on one or both sides of the above-mentioned composite material. As a method for forming the metal layer, sputtering, plating, pressure bonding of metal foil, bonding by heating and pressure, lamination, etc. are listed. As mentioned above, it is more preferable to heat and pressurize the metal layer onto the composite material by passing a resin film that will become a resin layer in between.

[0124] The pressure during the metal layer formation process is typically 0.01 MPa or higher, preferably 0.10 MPa or higher, more preferably 0.50 MPa or higher, even more preferably 0.80 MPa or higher, particularly preferably 1.00 MPa or higher, typically 50 MPa or lower, preferably 40 MPa or lower, more preferably 30 MPa or lower, even more preferably 20 MPa or lower, and particularly preferably 10 MPa or lower. When within the above ranges, peeling of the metal layer, etc., can be effectively suppressed, and as a composite material, a good relative permittivity, etc., can be ensured.

[0125] The temperature during the metal layer formation process is typically 250°C or higher, preferably 280°C or higher, more preferably 300°C or higher, even more preferably 320°C or higher, particularly preferably 340°C or higher, typically 500°C or lower, preferably 480°C or lower, more preferably 460°C or lower, even more preferably 440°C or lower, and particularly preferably 420°C or lower. When within the above ranges, peeling of the metal layer, etc., can be effectively suppressed, and as a composite material, a good relative permittivity, etc., can be ensured.

[0126] The heating and pressurizing time in the metal layer formation process is typically 1 second or more, preferably 30 seconds or more, more preferably 1 minute or more, further preferably 2 minutes or more, particularly preferably 3 minutes or more, typically 180 minutes or less, preferably 120 minutes or less, more preferably 60 minutes or less, further preferably 30 minutes or less, and particularly preferably 20 minutes or less. When within the above ranges, peeling of the metal layer, etc., can be effectively suppressed, and as a composite material, a good relative permittivity, etc., can be ensured.

[0127] As devices used for heating and pressurizing in the metal layer formation process, examples include presses, hot roller laminators, and belt presses.

[0128] Cooling during the metal layer formation process is preferably performed slowly, typically at a rate of 5°C / min or less, preferably 3°C / min or less, more preferably 2°C / min or less, even more preferably 1°C / min or less, typically at 0.01°C / min or more, preferably 0.05°C / min or more, and more preferably 0.1°C / min or more. When within the above range, the residual strain generated during cooling is reduced, thus suppressing the stretching caused by strain release due to etching, thereby suppressing dimensional changes during circuit fabrication.

[0129] The patterning process is a process of patterning a metal layer. As a patterning method, etching, a well-known technique, can be used. As an etching method, either wet etching or dry etching can be used. From the point of view of production efficiency, wet etching can be cited as an example.

[0130] Wet etching, for example, involves placing the covered portion (masking tape, photoresist, etc.) on a metal layer in a manner corresponding to the patterned portion and the non-patterned portion, and then using an etching solution to etch the metal layer (non-patterned portion) exposed from the covered portion.

[0131] Examples of etching solutions include hydrochloric acid, sulfuric acid, nitric acid, acetic acid, oxalic acid, phosphoric acid, and mixtures thereof, with ferric chloride aqueous solution being preferred. One or more of these solutions may be used. The coated portion is then removed from the upper surface of the metal layer by, for example, stripping.

[0132] To ensure good relative permittivity, fluorinated resins are used as insulating materials. However, fluorinated resins are prone to dimensional changes due to etching during circuit fabrication. These dimensional changes can cause short circuits when creating vias or other openings that deviate from their designed positions. The composite material of this embodiment, by having a specific tensile modulus of elasticity, reduces residual strain generated during cooling. Therefore, it exhibits minimal dimensional changes due to etching and lamination during circuit fabrication, allowing for precise placement of heat transfer components according to the design and enabling efficient circuit fabrication.

[0133] The specific tensile modulus of elasticity in this embodiment can be achieved by appropriately selecting the aforementioned manufacturing processes such as the "molding process," "rolling process," "heat compression process," "resin layer formation process," and "metal layer formation process," and can be more preferably achieved by controlling the cooling rate in these manufacturing processes. Furthermore, there is a tendency that the more the fluoropolymer resin is fiberized through each process, the greater the tensile modulus of elasticity of the final sheet-like composite material. The greater the shear force applied to the fluoropolymer resin, the more likely the fluoropolymer resin will fiberize. There are no particular limitations on the method for increasing the shear force applied to the fluoropolymer resin, and the following methods can be appropriately selected.

[0134] • In the molding process, increase the drawing ratio during paste extrusion (e.g., increase the RR of the FT die, etc.).

[0135] • Increase the number of rolling passes in the rolling process.

[0136] • In the rolling process, the number of stacking steps is increased, thus increasing the final number of constituent layers.

[0137] • In the rolling process, increase the rolling ratio (e.g., increase the thickness of the master sheet, or decrease the gap between the rolling rolls).

[0138] Example The following examples illustrate the invention in more detail, but appropriate modifications can be made without departing from the spirit of the invention. Therefore, the scope of the invention should not be limited by the specific examples shown below.

[0139] [Example 1] As an inorganic particulate aggregate, hydrophilic fumed silica (manufactured by Aerosil Corporation of Japan, model "AEROSIL50", BET specific surface area 50±15m²) was used. 2 As a surface modifier, triethoxy-1H,1H,2H,2H-tridecylfluoro-n-octylsilane (manufactured by Tokyo Chemical Industry Co., Ltd., model "T1770") was used for modification. Specifically, relative to 832.9 g of isopropanol, 40.8 g of surface modifier, 22.1 g of acetic acid, 43.2 g of pure water, and 80 g of inorganic microparticle aggregates were added, and the mixture was stirred for 24 hours to obtain a dispersion of inorganic microparticle aggregates. Next, the dispersion was heated at 100°C for 1 hour, and then at 200°C for 2 hours to obtain surface-modified inorganic microparticle aggregates.

[0140] Next, fused silica (Denka, model "SFP-130MC", BET specific surface area 6.2 m²) was used as non-porous inorganic microparticles. 2 As a surface modifier, triethoxy-1H,1H,2H,2H-tridecylfluoro-n-octylsilane (manufactured by Tokyo Chemical Industry Co., Ltd., model "T1770") was also used for modification.

[0141] Specifically, relative to 83.3 g of isopropanol, 6.8 g of surface modifier, 2.1 g of acetic acid, 4.3 g of pure water, and 80 g of non-porous inorganic microparticles were added, and the mixture was stirred for 24 hours to obtain a dispersion of non-porous inorganic microparticles. Next, the dispersion was heated at 100°C for 1 hour, and then at 200°C for 2 hours to obtain surface-modified non-porous inorganic microparticles.

[0142] Next, using a high-speed flow mixer, polytetrafluoroethylene (hereinafter sometimes simply referred to as "PTFE"), inorganic microparticle aggregates, non-porous inorganic microparticles, and volatile additives were mixed. Specifically, polytetrafluoroethylene (manufactured by Daikin, product number "Polyflon PTFE F-104", average particle size 550 μm) was prepared. Considering the amount of solids, polytetrafluoroethylene, surface-modified inorganic microparticle aggregates, and non-porous inorganic microparticles were added at a mass ratio of 38:37:25. The mixture was stirred and mixed at 14 m / sec and 24°C for 1 minute. Then, hydrocarbon oil (manufactured by Exxon Mobil, product number "Isopar M") was added as a volatile additive, so that when the total mass of polytetrafluoroethylene, inorganic microparticle aggregates, and non-porous inorganic microparticles was set to 100%, it became 65% by mass. The mixture was stirred and mixed at 3 m / sec and 24°C for 5 minutes to obtain a paste.

[0143] In the forming process, the paste extruded from the extruder is passed through a pair of rolling rolls to form an elliptical master sheet (sheet-shaped molded body) with a thickness of 3 mm, a width of 10-50 mm, and a length of 150 mm. Multiple master sheets are produced. Next, in the rolling process, two master sheets are stacked with their rolling directions aligned. The stack is then passed between the rolling rolls while maintaining the previous rolling direction to produce multiple first rolled stack sheets. Next, four first rolled stack sheets are stacked with their rolling directions aligned and rolled in the same direction to produce a second rolled stack sheet. This process of stacking and rolling sheets is repeated a total of 5 times, starting from the stacking and rolling of the master sheets, to produce a third rolled stack sheet (consisting of 512 layers). Next, four third-rolled laminated sheets are stacked. With the sheet surfaces parallel, the laminated sheets are rotated 90 degrees from the previous rolling direction and rolled through the gap between the rolling rolls. The gap between the rolling rolls is reduced by 0.5 mm each time, and this rolling process is repeated multiple times to obtain a sheet with a thickness of approximately 100 μm. The resulting rolled laminated sheet is heated at 150°C for 20 minutes to remove volatile additives, producing a sheet-like composite material.

[0144] Next, in the resin layer formation process, Fluon (registered trademark) PTFE dispersion AD939E (manufactured by AGC, 60% by mass solids) is impregnated onto one side of a polyimide carrier with a WET thickness of 4 μm. The coating is heated at 150°C for 5 minutes and then at 380°C for 5 minutes to create a resin film as the resin layer. A Cu foil (JX Metals, model "BHFX-HS-92F") is prepared to form the metal layer. The resin film and Cu foil are laminated, and the film is pressed at 6 MPa and 360°C for 10 minutes using a press to create a resin-metal sheet. Next, in the metal layer formation process, this resin-metal sheet and the aforementioned sheet-like composite material are laminated, and the film is pressed at 360°C for 5 minutes at 4 MPa to create a laminate with the metal layer. Then, the film is cooled to 23°C at a cooling rate of 1°C / min to obtain a composite material with a metal layer (copper-clad laminate).

[0145] [Example 2] In Example 1, the shear force applied to the fluorinated resin material in the molding and rolling processes was changed to the tensile modulus as described in Table 1. Otherwise, a composite material with a metal layer (copper-clad laminate) was obtained by the same method as in Example 1.

[0146] [Example 3] In Example 1, the thickness of the sheet-like composite material was changed from 100 μm to 380 μm, and the shear force applied to the fluorinated resin material in the molding and rolling processes was changed in such a way as to achieve the tensile modulus of elasticity described in Table 1. Otherwise, a composite material with a metal layer (copper-clad laminate) was obtained by the same method as in Example 1.

[0147] [Example 4] In Example 3, the shear force applied to the fluorinated resin material in the molding and rolling processes was changed to the tensile modulus of elasticity described in Table 1. Otherwise, a composite material with a metal layer (copper-clad laminate) was obtained by the same method as in Example 3.

[0148] [Example 5] In Example 3, the shear force applied to the fluorinated resin material in the molding and rolling processes was changed to the tensile modulus of elasticity described in Table 1. Otherwise, a composite material with a metal layer (copper-clad laminate) was obtained by the same method as in Example 3.

[0149] [Example 6] In Example 1, the process was carried out in the same manner as in Example 1 until the paste was adjusted before the molding process, and a paste was obtained.

[0150] Using the obtained paste, a roll-to-roll rolling process is employed, maintaining a constant tension (extraction / winding) of ±10% in the TD / MD directions as shown in Table 1, and performing multi-stage rolling. The multi-stage rolling process is described below.

[0151] The paste obtained above is used to make long strips with a thickness of 2 mm, a width of 300 mm, and a length of 10 m using an extrusion molding machine. Multiple roll sheets are then made and wound onto rollers. Using the two roll sheets obtained, multiple first roll rolled laminates with a two-layer structure are made by passing them through stacking rolls under tension (extraction / winding) within the range specified in Table 1 to a degree that does not cause breakage or wrinkling of the long strips.

[0152] Next, using the two obtained first rolled laminates, multiple second roll-shaped rolled laminates with a total of 4 layers are produced by passing them through the laminated rolling rolls at the tension (extraction / winding) described in Table 1.

[0153] Thus, by repeatedly performing a series of processes of stacking the sheets and passing them through the rolling rolls, a rolled third roll sheet (consisting of 2048 layers) is produced.

[0154] Next, the resulting third-roll rolled laminate is continuously passed through multiple rolls that gradually narrow in stages with a roll gap ranging from 0.5 mm to 0.05 mm, ultimately yielding a rolled laminated agglomerate sheet with a thickness of approximately 125 μm. This sheet is then passed through a drying oven heated to 150°C to remove volatile additives, and is wound as a continuous sheet-like composite material onto the final winding roll.

[0155] Next, in the resin layer formation process, Fluon (registered trademark) PTFE dispersion AD939E (manufactured by AGC, 60% by mass solids) is impregnated onto one side of a polyimide carrier with a WET thickness of 4 μm. The coating is then heated at 150°C for 5 minutes and then at 380°C for 5 minutes to create a resin film. A Cu foil (JX Metals, model "BHFX-HS-92F") is prepared to form the metal layer. The resin film and Cu foil are laminated, and the film is pressed at 6 MPa and 360°C for 10 minutes using a press to create a resin-metal sheet. Next, in the metal layer formation process, this resin-metal sheet is laminated with the aforementioned sheet-like composite material and pressed at 360°C for 5 minutes at 4 MPa to create a laminated sheet with the metal layer.

[0156] Then, it was cooled to 23°C at a cooling rate of 4.5°C / min to obtain a composite material with a metal layer (copper-clad laminate).

[0157] [Examples 7, 8] In Example 6, a composite material with a metal layer (copper-clad laminate) was obtained by the same method as in Example 6, except that the tension (drawing / winding) described in Table 1 was kept constant within ±10% in the TD direction / MD direction.

[0158] [Comparative Example 1] In Example 1, a composite material with a metal layer (copper-clad laminate) was obtained by the same method as in Example 1, except that the cooling rate of the laminated sheet with the metal layer was changed to cool to 23°C at 4.5°C / min.

[0159] Each of the obtained composite materials with a metal layer was immersed in a 38 mass% ferric chloride aqueous solution (manufactured by SUNHAYATO Co., Ltd., etching solution H-200A) for 30 minutes to remove the resin-metal sheet, then washed with pure water and dried to obtain a plate-shaped composite material. The tensile elastic modulus of the plate-shaped composite material was measured as described below. The results are shown in Table 1. In addition, the porosity of the plate-shaped composite material was measured as described below, and as a result, the porosity of Examples 1 to 8 was 34% by volume.

[0160] <Tensile Elastic Modulus in MD Direction and TD Direction> The tensile elastic modulus of the plate-shaped composite material was measured in accordance with the method specified in Japanese Industrial Standard JIS K7161. More specifically, a desktop precision universal testing machine Autograph AGS-X (manufactured by Shimadzu Corporation) was used as the tensile testing machine, and a tensile test was performed on a test piece prepared in dumbbell No. 1 shape or dumbbell No. 2 shape (width of the parallel part: 10 mm) under the measurement conditions of a measurement temperature of 25°C, a tensile speed of 100 mm / min, and an initial distance between chucks of 10 mm.

[0161] It should be noted that, regarding the test pieces, a test piece for tension in the MD direction and a test piece for tension in the TD direction were prepared for each experimental example and the test was carried out.

[0162] Then, the maximum tensile force recorded until the test piece was broken was determined, the value obtained by dividing it by the cross-sectional area of the test piece was defined as the tensile strength (unit: MPa), and the slope of the stress / strain curve corresponding to the two points of 0.05% and 0.25% strain during the tensile test was defined as the tensile elastic modulus (unit: MPa).

[0163] <Porosity> The volume of the composite material, the specific gravity and mass (blending mass) of polytetrafluoroethylene (PTFE), the specific gravity and mass (blending mass) of the inorganic fine particle aggregate, the specific gravity and mass (blending mass) of the non-porous inorganic fine particles, and the specific gravity and mass (blending mass) of other fillers were measured, and the porosity was calculated by substituting into the following formula.

[0164] Porosity (volume %) = [Volume of composite material - (Mass of PTFE / Specific gravity of PTFE) - (Mass of inorganic microparticle aggregates / Specific gravity of inorganic microparticle aggregates) - (Mass of non-porous inorganic microparticles / Specific gravity of non-porous inorganic microparticles) - (Mass of other fillers / Specific gravity of other fillers)] / Volume of composite material × 100 In addition, for each of the obtained composite materials with metal layers (copper-clad laminates), the dimensional changes were measured as described below. The results are shown in Table 1.

[0165] <Size Changes> The dimensional change rate was calculated by measuring the distance from the origin to the measurement point before and after etching the copper-clad laminate. The specific details are as follows, and the results are shown in Table 1.

[0166] It should be noted that the etching is performed as follows: the metal layer is immersed in a 38% by mass ferric chloride aqueous solution (SUNHAYATO, etching solution H-200A) for 30 minutes to pattern the metal layer. After partially removing the metal layer (resin metal sheet), it is rinsed with pure water and then dried.

[0167] (Rate of dimensional change in the MD direction) When the origin and a point moved 40 mm from the origin in the MD direction are taken as measurement points, the distance (40 mm) from the origin before etching to the measurement point is set as "MDx".

[0168] Next, etching is performed with no etching at the origin and etching at the measurement point. The etching boundary line is used to reach the midpoint between the origin and the measurement point. The distance from the etched origin to the measurement point is measured as "MDy". Substituted into the following formula, the absolute value of the dimensional change rate in the MD direction is calculated.

[0169] Dimensional change rate (ppm) = |(MDx - MDy) / MDx × 100 6 | (Rate of dimensional change in the TD direction) When the origin and a point moved 60 mm from the origin in the TD direction are taken as the measurement points, the distance (60 mm) from the origin before etching to the measurement point is set as "TDx".

[0170] Next, etching is performed with no etching at the origin and etching at the measurement point. The boundary line between the etched and unetched points is used to reach the midpoint between the origin and the measurement point. The distance from the etched origin to the measurement point is measured as "TDy". By substituting into the following formula, the absolute value of the dimensional change rate in the TD direction is calculated.

[0171] Dimensional change rate (ppm) = |(TDx-TDy) / TDx×1006 | [Table 1] Examples 1 to 6, where the tensile modulus of elasticity is below a specific value, all exhibit low dimensional change rate and excellent dimensional stability.

[0172] On the other hand, Comparative Example 1, whose tensile modulus of elasticity exceeds a certain value, exhibits large dimensional changes and is not suitable for use as a product.

[0173] Furthermore, Examples 6-8, which control the tension during extraction / winding to an appropriate level, reduce internal residual stress generated during multi-stage rolling, and suppress dimensional changes even with quenching at 4°C / min or higher without slow cooling. It should be noted that Examples 1-5 involve rolling without tension control.

[0174] The above embodiments illustrate specific aspects of the present invention, but these embodiments are merely illustrative and not intended to be limiting. Various modifications that will be apparent to those skilled in the art are within the scope of this invention.

[0175] Industrial availability The composite material, as one aspect of the present invention, can be used as a circuit board for mobile phones, computers, etc., and a substrate for microstrip patch antennas for millimeter-wave radar, etc.

Claims

1. A plate-shaped composite material, wherein, The composite material contains fluorinated resin and filler, and has pores within it. The tensile modulus of elasticity of the composite material is below 230 MPa.

2. The plate-shaped composite material according to claim 1, wherein, The fluorinated resin is polytetrafluoroethylene.

3. The plate-shaped composite material according to claim 1 or 2, wherein, The filler is silicon dioxide.

4. The plate-shaped composite material according to claim 3, wherein, The silica contains fumed silica and molten silica.

5. A composite material with a metal layer, wherein, At least one side of the plate-shaped composite material as described in any one of claims 1 to 4 has a metal layer.

6. A method for manufacturing a composite material with a metal layer, comprising the method for manufacturing the composite material with a metal layer as described in claim 5, wherein, The process includes: laminating a metal layer onto a plate-shaped composite material; bonding by heating and pressurizing; and cooling at a rate of less than 1°C per minute.

7. A method for manufacturing a composite material with a metal layer, comprising the method for manufacturing the composite material with a metal layer as described in claim 5, wherein, The process includes the following steps: rolling a sheet-like composite material while maintaining tension before the metal layers are laminated, such that the pull-out tension relative to the MD direction is 10N or more and 50N or less, and the winding tension is 10N or more and 20N or less, and the pull-out tension relative to the TD direction is 20N or more and 80N or less, and the winding tension is 10N or more and 20N or less; laminating metal layers on the sheet-like composite material; bonding by heating and pressurizing; and cooling at a cooling rate of 5°C or less per minute.

Citation Information

Patent Citations

  • Composite material for electrical use, laminated sheet and printed wiring board

    JP1991212987A

  • Dielectric composite

    JP1994119810A